PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS FLIPBOOK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH MENENGAH ATAS(SMA) - Yuyun Ariyanto; Muhammad Akhyar, Djono (Prosiding Seminar Nasional Indonesia, 2024)
In the field of education, technological developments which are currently running rapidly are certainly experiencing fundamental changes that occur in the education evaluation system at the educational unit level. This research was conducted with the aim of finding out the effectiveness of flipbook-based mathematics teaching modules in improving the critical thinking skills of high school (SMA) students, with the subjects of this research being class XI students at SMA MTA Surakarta. Data was collected using questionnaires, interviews and mathematics test questions on the topic of linear programming. The data obtained was then analyzed using quantitative analysis. The results of this research explain that the flipbook-based learning module to improve the critical thinking skills of class Based on this, the flipbook-based mathematics learning module to improve critical thinking skills in class XI students at SMA MTA Surakarta can be used in educational units with appropriate characteristics. The use of this flipbook is not limited to student worksheets but the entire mathematics learning module in flipbook form.